Biomechanical research in figure skating: a literature review - Koga, A.; Liu, J. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Biomechanical analysis is one of the most used procedures for sport performance optimization, injury reduction and equipment development. Figure skating is one of the most popular sports in winter Olympic sport categories. Despite its competitiveness and high risks of injuries, to the author`s knowledge, no review study of biomechanical research in figure skating has been conducted yet. Therefore, the purpose of this study is to provide an overview of existing biomechanical research in figure skating. METHODS: Articles were searched in reliable databases such as PubMed, Web of Science (WOS) Core Collection. The search were completed in May 2023 by using year range of 2000~ 2023 and searching keywords including figure skat* and biomechanic*. Only English, full-text and original research articles were selected. Total of 13 articles out of 42 were topic related papers were included in this study. Then, two more articles were added from additional search using keywords, plantar pressure and muscular activation. RESULTS: Result of annual trends analysis shows no rapid growing trend of publications from 2000 until 2023, however; a very visible increase in 2015 is observed. Out of 15 articles, kinematic analysis of figure skating jumps accounts for the majority of biomechanical research done by researchers. The increase in rotational velocity in air, vertical velocity at take - off, subsequent time in air, greater knee-hip angle of the supporting leg and decrease the angle of jump take-off are commonly observed in higher level jumps (1). Kinetic analysis in figure skating are mostly focused on the effect of different skating equipment including insoles, skates, blades on skater`s body and performance. Only one article utilized pressure insole to examine the landing impact on lower extremity caused by jumps, which is published in 1997 (2). Moreover, in recent 20 years, only one research assessed muscular activation patterns during different jumps. Higher plantar pressures and stronger lower extremity muscle activations were observed in jumps with more rotations (3). CONCLUSION: The findings of this study suggest that recent biomechanical research on figure skating have mostly focused on kinematic analysis of figure skating jumps, and very limited number of studies evaluate electromyography (EMG) activation pattern of muscles during jumping movements to explore the force generation and impact on the lower limbs. Also in the future, more studies on plantar pressure pattern during elements take-off and landing can potentially provide deeper understanding in both jump and spin take-off techniques include correct power execution methods, foot weight distribution for better balancing to not only optimize athletes` performances but also to reduce potential lower extremity injuries. better balance.